PENERAPAN METODE FORECASTING DALAM MEMPREDIKSI JUMLAH MAHASISWA BARU MENGGUNAKAN ALGORTIMA SIMPLE LINIER REGRESSION - Simatupang, Julianto (Jurnal Tekinkom (Teknik Informasi dan Komputer), 2024)
Admission of new students is an annual activity carried out by universities, therefore it requires special preparation and handling regarding this activity. It is not uncommon for universities to have to prepare teams in advance so that implementation can be optimal. However, it cannot be denied that the majority of universities only focus on administrative matters without trying to dig up information from big data on the history of new student registration in the previous year, so that it can be used as a source of new information to determine targets and estimate the number of new students. Seeing this problem, the researcher intends to propose a solution to the problem in determining estimates of new student admissions using the forecasting method using the Simple Linear Regression Algorithm. The application of these methods and algorithms is able to provide solutions in estimating/forecasting recommendations for new students who will enter AMIK Mahaputra Riau College in the following academic year